Anthropometric and physical fitness components comparison between high- and low-performance archer - Lau, J. S.; Ghafar, R.; Hashim, H. A.; Zulkifli, E. Z. (Annals of Applied Sport Science, 2020)
Background. Archery is a sport that demands a high level of fitness due to its long hours of training and competitive nature. Thus, archers need to have high fatigue tolerance and body figure to perform successfully. Objectives. This study aims to compare and correlate the anthropometric and physical fitness variables on archery shooting performance. Methods. Participants were youth archers of the Terengganu state team and Malaysia Pahang Sports School from Malaysia (n=12; male: 9 and female: 3; Mean age: 16.0±1.6 years). They were divided into two groups (high-performance, HPA, and low-performance, LPA) based on their preliminary archery score obtained in the early stage of the study. The archery shooting performance was assessed by total shooting score (36 arrows shot from 70 meters distance). Anthropometric (height, body mass, body mass index, body fat percentage, skeletal muscle mass, and arm span), muscular strength and endurance, flexibility, balance, and aerobic fitness were assessed. Results. Mann-Whitney test showed that height, arm span, handgrip strength, and predicted VO2max showed significant differences between the groups (p<0.05). Spearman correlation showed that height, arm span, right-hand grip, and predicted VO2max significantly correlated with scores (r=0.80, 0.82, 0.61, 0.68). Conclusion. The result showed that archers with higher height and longer arm span have more advantages in archery. In terms of fitness level, muscular strength and aerobic capacity are essential for the archer to excel in this sport. This finding helps coaches and team managers when conducting talent identification programs and training programs for athletes.